Mandibular assessment of panoramic radiographs for sex identification - Alana Lima dos Santos; Kennya Thaís Sabino Pinheiro; Lúcio Mitsuo Kurita; Esther Carneiro Ribeiro; Paulo Goberlânio de Barros Silva; Fábio Wildson Gurgel Costa; Andréa Silvia Walter de Aguiar (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Sex determination plays a crucial role in the post-mortem identification of human remains. One effective approach for obtaining sex-related data is to use measurements of anatomical structures such as the mandible. This study aimed to evaluate the potential of mandibular radiomorphometric indices from panoramic radiographs (PRs) for the identification of sexual dimorphism. The study sample included 300 PRs of individuals aged 51 to 80 years from the northeastern region of Brazil. Four linear measures and three numerical indices were analyzed with Inkscape® version 1.0.1 for Windows by two blinded evaluators. After statistical analysis, the results showed that the linear measurements obtained from PRs are a reliable method for sex identification. However, the calculated indices of these measurements exhibited lower efficacy for the same purpose. Therefore, PRs proved to be a valuable method for sexual identification through mandibular assessment.